(3GdETQGa Ydi ePGgH GdETQGas - (3jMji Hf (B((3gHjQI Hf(B) (3eMeO Hf gHjQI GdPgdj GdTjHGfqj, CHh GdeXaQ, Yhf GdOjf,J (B560 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdWgGQI Hbhdg (B: (3GdMeO ddg Mb MeOg CLeYhG Ydi Cf GdUdGI dG JUM EdG HWgGQI EPG hLO GdSHjd EdjgG s
(3BNQgG (B:s
(3jfJgi HHGH GdbVGA (B( (3ef cJGH (B( (3GdEjeGf (B) (3Hbhdg (B: (3hGdeaghe ef gPG Cf GdSdGeI ai ehGWf GdENJdGa Hjf GdCeI GdJeSc HeG GLJeYhG Ydjg Je GdcJGH HMeO Gddg s
(3GdfSNI HgG MhGTs
(3cJHJ GdfSNI HNW Hg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B175 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B228s
Keywords: (3abg GdePGgH GdCNQis